2017
DOI: 10.1080/1028415x.2017.1288340
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological symptoms and aspartame: What is the connection?

Abstract: Aspartame (α-aspartyl-l-phenylalanine-o-methyl ester), an artificial sweetener, has been linked to behavioral and cognitive problems. Possible neurophysiological symptoms include learning problems, headache, seizure, migraines, irritable moods, anxiety, depression, and insomnia. The consumption of aspartame, unlike dietary protein, can elevate the levels of phenylalanine and aspartic acid in the brain. These compounds can inhibit the synthesis and release of neurotransmitters, dopamine, norepinephrine, and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 106 publications
0
53
0
1
Order By: Relevance
“…To the best of our knowledge, no investigation in humans has been conducted to explore the specific role of food additives for the risk of depression except concerning artificial sweeteners. Some experimental studies argue for a modulating role of artificial sweeteners, such as aspartame, on neurotransmitters regulation which may lead to symptoms such as mood or depression [49]. However, a recent review based on more than 370 scientific papers reported that data are currently insufficient to conclude [50].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no investigation in humans has been conducted to explore the specific role of food additives for the risk of depression except concerning artificial sweeteners. Some experimental studies argue for a modulating role of artificial sweeteners, such as aspartame, on neurotransmitters regulation which may lead to symptoms such as mood or depression [49]. However, a recent review based on more than 370 scientific papers reported that data are currently insufficient to conclude [50].…”
Section: Discussionmentioning
confidence: 99%
“…As consumption of foods and beverages sweetened with LNCS has increased, questions about their benefits and possible adverse effects on health have also arisen [ 76 , 77 ]. Some studies have investigated potential short-term effects, for example on food intake, mood or blood pressure [ 78 , 79 , 80 ].…”
Section: Lncs Role In Body Weight Management and In Chronic Diseasmentioning
confidence: 99%
“…62,63 It is also possible that artificial sweeteners alter neurotransmitter synthesis and release, as well as inducing oxidative stress. 64 In addition, studies have found that artificial sweeteners and sugar substitutes such as xylitol can increase Bifidobacteria in the gut. People with PD often have higher levels of Bifidobacteria in the first place.…”
Section: Artificial Sweetenersmentioning
confidence: 99%